2012
DOI: 10.1111/j.1600-0501.2012.02536.x
|View full text |Cite
|
Sign up to set email alerts
|

Cleaning and modification of intraorally contaminated titanium discs with calcium phosphate powder abrasive treatment

Abstract: Using the air powder abrasive method with calcium phosphate powders on contaminated titanium discs, an efficient implant cleaning and surface modification can be achieved. This method should be further improved as it has possible potential to be used as an implant surface treatment method for implants involved with peri-implantitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
63
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 34 publications
8
63
0
Order By: Relevance
“…As to the above-mentioned methods, the efficacy of ultrasonic curettage seems to underly the use of air polishing systems (Figure 3) [5,62,64-68]. Persson et al and Renvert et al experienced significantly lower numbers of bacteria with partial reduction of plaque and bleeding scores after mechanical curettage, while Schwarz et al reported 30%-40% less residual biofilm areas by using ultrasonic methods [5,63,66].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As to the above-mentioned methods, the efficacy of ultrasonic curettage seems to underly the use of air polishing systems (Figure 3) [5,62,64-68]. Persson et al and Renvert et al experienced significantly lower numbers of bacteria with partial reduction of plaque and bleeding scores after mechanical curettage, while Schwarz et al reported 30%-40% less residual biofilm areas by using ultrasonic methods [5,63,66].…”
Section: Reviewmentioning
confidence: 99%
“…The results of air polishing systems are depending on the used medium and are significantly better in the following order: hydroxylapatite/tricalcium phosphate > hydroxylapatite > glycine > titanium dioxide > water and air (control group) > phosphoric acid [64]. …”
Section: Reviewmentioning
confidence: 99%
“…In fact, there are many methods for surface treatment and modification. The ion implantation [7], powder abrasive treatment [8], laser irradiation [9], plasma spraying [10] and modification with nanoparticles [11] are named as the most popular approaches.…”
Section: Introductionmentioning
confidence: 99%
“…7 Tastepe et al in a recent review concluded that the in vivo data on air powder abrasive treatment as an implant decontamination is not sufficient to draw definitive conclusions. 8 3. The Use of Lasers:-Salmeron et al in an animal model have studied laser therapy alone or with photodynamic therapy and compared them to both negative and positive controls for implant surface decontamination.…”
mentioning
confidence: 99%